An online survey on clinical characteristics of otologic symptoms linked to COVID-19 infection - Wu, Linsui; Peng, Hongyi; He, Yufeng; Pu, Ling; Zhong, Shixun (Frontiers in Public Health, 2023)
(1) Objective: To report the otologic symptoms that present in patients with COVID‐19 infection and investigate the pathogenic characteristics during the period of the pandemic; (2) Materials and Methods: This cross-sectional descriptive study included participants with COVID-19 infection. COVID-19 infection was verified in these patients by nucleic acid test or antigen test. An online questionnaire was developed to analyze the association between the COVID-19 pandemic and the characteristics of otologic symptoms; (3) Results: This study included 2247 participants, of which nearly half had one or more otologic symptoms. The presents of otologic symptoms were associated with gender(OR=1.575, p<0.0001), age(OR=0.972, p<0.0001), and occupation(healthcare worker: p<0.0001; personnel of enterprises or institutions: OR=1.792, p<0.0001; student: OR=0.712, p<0.044). The otologic symptoms following COVID-19 infection in order were vertigo(25.95%), tinnitus (19.05%), otalgia(19.00%), aural fullness(17.18%), hearing loss(11.62%), otorrhea(1.25%), and facial paralysis(0.27%); (4) Conclusions: The present study shows that otologic symptoms are common among the COVID-19 infected participants and that these symptoms mostly recover spontaneously. During the corona-virus pandemic, the involvement of the cochleovestibular system and facial nerve should not be overlooked while treating the COVID-19 infected individuals.